Managing the Ageing Workforce in the East and the West. - Flynn, Matt (Changing context of managing people., 2017)
This book brings together Eastern and Western perspectives to explore human resource interventions into extending working life, including phased retirement, healthy work environments and lifelong learning. It assesses issues of implementation in differing cultural, intergenerational, institutional and family contexts.